Nivel de ventas y su incidencia en la rentabilidad de la empresa Reina del Cisne.” - Macías Triguero, Byron Geovanny (2017)
The company Reina del Cisne was legally constituted in 1991, initiates its banana production and marketing activities, the Hacienda is located in km 4 1/2 via Baba-Isla de Bejucal, here people work production, fruit care and harvest, to the administrative which are dedicated to offer the goods and commercial transaction